THE EFFECT OF ADDITION NON DENTAL GLASS FIBER TOWARDS THE FLEXURAL STRENGTH OF NANOFIL RESIN COMPOSITE - Dessy Adhira Nur Safitri; Eko Hadianto; Erdianto Setya Wardhana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Resin composite is one of many materials that are often used in daily dental practice because of its convenience and high aesthetic value. Resin composite consists of various materials, one of them is nanofil resin composite. Some research has shown that non-fiber resin composite has poor flexural strength. Therefore, fiber (FRC) can be added to the resin composite as a reinforcing material.Method: This study is based on a true-experimental, post-test only control group design with 16 specimen total of samples with 25x2x2 mm in the size. The samples were classified into two groups, the first group is the nanofil resin composite without the addition of non-dental glass fiber, and the second group is the nanofil resin composite with the addition of non-dental glass fiber. Data was tested using the parametric test, Independent T-test.Result: The average result of the flexural strength of the nanofil resin composite group without the addition of non-dental glass fiber was 102.7725 Mpa. As for the nanofil resin composite group with the addition of non-dental glass fiber is 166.1100 Mpa. The results of the independent T-test showed p-value = 0.000.Conclusion: It was found that nanofil resin composite with addition of non-dental glass fiber has a higher flexural strength than resin composite without addition of non-dental glass fiber so that it can be used as an alternative choice in applications in dentistry.